Enhancing asphalt pavement longevity through microcapsule-encapsulated rejuvenators: mechanical performance and self-healing evaluation - Gowda, Sachin; Behl, Ambika; Shanmuganathan, Kadhiravan; Gupta, Aakash (International Journal of Pavement Research and Technology, 2025)
Self-healing asphalt incorporating encapsulated rejuvenators presents a promising solution to extend pavement life by autonomously restoring binder functionality in aged or cracked regions. Calcium-alginate microcapsules encapsulating a commercially available bio-based rejuvenator available in the Indian market were synthesized (2–3 mm in diameter) and incorporated into Bituminous Concrete Grade-II asphalt mixtures at 0%, 0.5% and 1% (by aggregates weight). Capsules showed rupture strength > 18 N and thermal stability up to 200 °C. Microstructural (4D-XRM (X-ray Microscopy), Scanning Electron Microscopy (SEM), Brunauer-Emmett-Teller (BET)), chemical (Fourier Transform Infrared (FTIR), Energy-Dispersive X-ray Spectroscopy (EDAX), SARA) and mechanical (Indirect Tensile Strength (ITS), resilient modulus, dynamic creep, Semi-Circular Bending (SCB) healing) tests under unaged, short-term aged (STA) and long-term aged (LTA) conditions were performed. At 1% dosage, the Healing Index (HI) increased substantially (up to 58.03% for LTA), while volumetric, rutting and moisture resistance were not significantly affected. EDAX and SARA confirm targeted rejuvenator release under aging. These findings show that low dosages of Calcium alginate microcapsules can improve fracture recovery in aged asphalt mixtures without compromising initial performance, supporting their potential for self-healing pavements.